PENERAPAN MODEL PEMBELAJARAN FLIPPED CLASSROOM DENGAN VIDEO PEMBELAJARAN TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI LUAS BANGUN DATAR DI KELAS V SDN 84 SINGKAWANG - Liana; Rika Wahyuni; Mariyam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to: 1) determine the differences between the experimental class and the control class after the implementation of the flipped classroom learning model with learning videos on students' mathematical problem-solving abilities in class V of SDN 84 Singkawang, 2) determine whether the interest in learning mathematics is high after the implementation of the flipped classroom learning model with learning videos in class V of SDN 84 Singkawang. The type and design of the research used is experimental research with a Quasi Experiment design in the form of Post-test Only. The population in this study were class V students of SDN 84 Singkawang. The samples in this study were classes VA and VB which were used as the experimental class and the control class. Data analysis techniques in this study were normality tests, homogeneity tests, hypothesis tests using independent sample t-tests and percentages of student learning interests. Based on the results of the data analysis, it can be concluded that: 1) There is a difference in students' mathematical problem-solving abilities between students who applied the Flipped Classroom learning model with Learning Videos and students who applied the direct learning model, 2) Students' interest in learning is classified as very high after the application of the Flipped Classroom learning model with Learning Videos, an average score of 83.52 is obtained with a very high category.